2012
DOI: 10.1118/1.4745558
|View full text |Cite
|
Sign up to set email alerts
|

Biological effect of dose distortion by fiducial markers in spot‐scanning proton therapy with a limited number of fields: A simulation study

Abstract: Purpose: In accurate proton spot-scanning therapy, continuous target tracking by fluoroscopic X-ray during irradiation is beneficial not only for respiratory moving tumors of lung and liver but also for relatively stationary tumors of prostate. Implanted gold markers have been used with great effect for positioning the target volume by a fluoroscopy, especially for the cases of liver and prostate with the targets surrounded by water-equivalent tissues.However, recent studies have revealed that gold markers can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Also, the time structure of the synchrotron is modeled based on specification given by the manufacturer, which may be too simplified as compared to the actual system. The other shortcoming is that the simulation studies have been performed using rigid model, influenced by the small fiducial to the dose distribution [7], minute change around the tumor and fiducial, phase control of the log data and beam delivery in each simulation. The above are the main concerns that we need to address in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the time structure of the synchrotron is modeled based on specification given by the manufacturer, which may be too simplified as compared to the actual system. The other shortcoming is that the simulation studies have been performed using rigid model, influenced by the small fiducial to the dose distribution [7], minute change around the tumor and fiducial, phase control of the log data and beam delivery in each simulation. The above are the main concerns that we need to address in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, implanted fiducial markers for image-guided patient alignment have been used in proton therapy for many years (Gall et al , 1993; Welsh et al , 2004; Newhauser et al , 2007a; Newhauser et al , 2007c; Ptaszkiewicz et al , 2010; Matsuura et al , 2012). Substantial recent improvements in on-board imaging systems, patient positioning, and patient immobilization have led to increased use of radiopaque implanted fiducial markers in proton therapy to many disease sites, with the goal of improving target coverage and/or normal tissue sparing.…”
Section: Proton Interaction Mechanismsmentioning
confidence: 99%
“…Several studies reported that implanted metallic fiducials can cause dose shadows that may compromise local tumor control for certain diseases, e.g. , prostate carcinoma and uveal melanoma (Newhauser et al , 2007a; Newhauser et al , 2007c; Giebeler et al , 2009; Cheung et al , 2010; Huang et al , 2011; Matsuura et al , 2012; Zhang et al , 2012; Carnicer et al , 2013). …”
Section: Proton Transport Calculationsmentioning
confidence: 99%
“…Since SSPT does not require compensators and collimators, SSPT is suitable for multiple beam treatment. In a previous study, the effect of gold markers was found to be biologically negligible if multiple beams were used to irradiate the target [18].…”
Section: Discussionmentioning
confidence: 94%